Tracking Electron Uptake from a Cathode into Shewanella Cells: Implications for Energy Acquisition from Solid-Substrate Electron Donors - Annette R. Rowe (American Society for Microbiology, 2018)
ABSTRACT While typically investigated as a microorganism capable of extracellular electron transfer to minerals or anodes, Shewanella oneidensis MR-1 can also facilitate electron flow from a cathode to terminal electron acceptors, such as fumarate or oxygen, thereby providing a model system for a process that has significant environmental and technological implications. This work demonstrates that cathodic electrons enter the electron transport chain of S. oneidensis when oxygen is used as the terminal electron acceptor. The effect of electron transport chain inhibitors suggested that a proton gradient is generated during cathode oxidation, consistent with the higher cellular ATP levels measured in cathode-respiring cells than in controls. Cathode oxidation also correlated with an increase in the cellular redox (NADH/FMNH2) pool determined with a bioluminescence assay, a proton uncoupler, and a mutant of proton-pumping NADH oxidase complex I. This work suggested that the generation of NADH/FMNH2 under cathodic conditions was linked to reverse electron flow mediated by complex I. A decrease in cathodic electron uptake was observed in various mutant strains, including those lacking the extracellular electron transfer components necessary for anodic-current generation. While no cell growth was observed under these conditions, here we show that cathode oxidation is linked to cellular energy acquisition, resulting in a quantifiable reduction in the cellular decay rate. This work highlights a potential mechanism for cell survival and/or persistence on cathodes, which might extend to environments where growth and division are severely limited. IMPORTANCE The majority of our knowledge of the physiology of extracellular electron transfer derives from studies of electrons moving to the exterior of the cell. The physiological mechanisms and/or consequences of the reverse processes are largely uncharacterized. This report demonstrates that when coupled to oxygen reduction, electrode oxidation can result in cellular energy acquisition. This respiratory process has potentially important implications for how microorganisms persist in energy-limited environments, such as reduced sediments under changing redox conditions. From an applied perspective, this work has important implications for microbially catalyzed processes on electrodes, particularly with regard to understanding models of cellular conversion of electrons from cathodes to microbially synthesized products.